Relacje zachodzące pomiędzy miejską rodziną małą a rodziną dużą - Żurek, Aldona (Wydawnictwo Naukowe UAM, 2001)
In this paper undertaken became problem of relating account which one hold municipal families with relatives. Thought industrializing peoples make new demands on kin, industrialization also makes possible to respond to family claims with new resources. Nuclear family unite with large family intensive and complicated social ties. It accepts emotional, instrumental and normative character. Social interactions connect members of family lean more and more often, for executed free choice and rule of reciprocity. Only connections accounts of parents and of children and siblings have stood solid character more and more greater. Meaning, behaving to most of aspects of life o f individual, have other informal groups. Healthy relationships in large family include companionship, security and feeling of well - being.
Relations in the nuclear and extended city family